Influence of the Technological Parameter and Die Structure on Metal Flow Line for Precision Forging Car Gear Blank - Li Tianxing; Zhang Xunlei; Fu Jianzhong; Gao Zhenshan; Wu Shuaibin; Yang Chao (Jixie chuandong)
Because of the complex structure of gear production,poor working conditions,high reliability requirements,and so on,the structure performance requirements for precision forging gear blanks become more stringent. Therefore,the metal flow line distribution state is gradually become an important indicator of car gear blanks performance test. The technological parameter and die structure have greatly effect on the direction of metal flow. The influence law of structure of the die and punch on metal flow line distribution state of car gear blanks is deeply analyzed by means of finite element simulation software DEFORM- 3D. The optimal technological parameter and mold structure size are determined. The actual production shows that the actual metal flow lines and product requirements are basically consistent. The method of pre- control optimization can effectively reduce the number of tests,reduce the production costs and increase the production efficiency. The important technical support for improvement of structure performance and mechanical behavior in mass precision forging of car gear blanks is provided.